Lateral vaccination against Newcastle disease in broilers : Effect of ratio and density - ., Darminto (Indonesian Animal Sciences Society, 1995)
Ratio (50%, 33% or 20% of directly vaccinated and in-contact vaccinated birds) and density (5 birds, 10 birds or 15 birds per square meter) for the effectiveness of lateral transmission of in-contact vaccination against Newcastle disease (ND) were evaluated in this study . The antibody patterns and the protection against challenge virus were used as criteria. Generally, antibody responses induced by direct vaccination showed higher titres compared to those induced by the in-contact vaccination, but at two week after the second vaccination, the differences were not significant. At the in-contact vaccinated birds, no significant difference (P>0 .05) was observed in the pattern of antibody development by ratio . However, group of vaccinated birds with the ratio of 20% tended to have lower protection . The results of the evaluation of density demonstrated that there was no effect of density (P>0 .05) to the pattern of antibody development, although the higher density seemed to have the higher protection. However, the density of 15 birds/m2 increasing the susceptibility to the other diseases. Based on the data obtained in this research, it could be concluded that (1) the optimal ratio for the effective lateral transmissibility is 33%, and (2) the optimal density for the effective lateral transmissibility is 10 birds/m2. Key words : Newcastle disease, in-contact vaccination, broilers